Spacer DNA sequences upstream of the T-A-T-A-A-A-T-A sequence are essential for promotion of H2A histone gene transcription in vivo. - Grosschedl, R (1980)
The control region of a sea urchin H2A histone gene may be functionally dissected into at least three DNA segments, which we have termed modulator, selector, and initiator elements. While the initiator and in particular the selector containing the T-A-T-A-A-A-T-A sequence are specificity elements that dictate the generation of faithful 5' ends to H2A mRNA, the modulators control the rate at which these specificity elements operate [Grosschedl, R. & Birnstiel, M. L. (1980) Proc. Natl. Acad. Sci. USA 77, 1432-1436]. By functional tests of in vitro mutated histone DNA in the Xenopus oocyte we have now discovered that the segment E of the A+T-rich spacer DNA lying at a considerable distance upstream of the conservative T-A-T-A-A-A-T-A sequence is a strong modulator element of H2A gene transcription. Deletion of this element creates a 15- to 20-fold H2A-specific down mutation. Segment E by itself cannot elicit initiation of transcription except in coordination with the prelude sequence of the H2A gene. The nucleotide sequence of the relevant spacer element showing modulator activity has been determined and found to contain a pattern of T and A runs as well as a series of inverted repeats. Additional pre-H2A spacer mutants, including a spacer inversion mutant, have been constructed in vitro, that, when injected into the oocyte nucleus, modulate the expression of the H2A gene by an overall factor as large as 100. Other factors controlling promoter activity are discussed.